Display of human and rabbit monocyte chemoattractant protein-1 on human embryonic kidney 293T cell surface - Maryam Boshtam; Seddigheh Asgary; Ilnaz Rahimmanesh; Shirin Kouhpayeh; Jamal Naderi; Zahra Hejazi; Hoda Mohammad-Dezashibi; Ina Laura Pieper; Hossein Khanahmad (Wolters Kluwer Medknow Publications, 2018)
Monocyte chemoattractant protein-1 (MCP-1/CCL2) is a protein that is secreted immediately upon endothelial injury, and thereby it plays a key role in inflammation via recruitment of leucocytes to the site of inflammation at the beginning and throughout the inflammatory processes. Aim of this study was to develop two separate cell lines displaying either human MCP-1 (HMCP-1) or rabbit MCP-1 (RMCP-1) on their surface. A DNA fragment containing HMCP-1- or RMCP-1-encoding sequence was inserted into a pcDNA plasmid. Escherichia coli cells strain TOP 10F' was separately transformed with the pcDNA/RMCP-1 or /HMCP-1 ligation mixture. Following the cloning and construct verification, human embryonic kidney cell line (HEK 293T) was transfected with either of the linearized plasmids. Plasmid integration into the genomic DNA of HEK 293T cells was verified by polymerase chain reaction (PCR). HMCP-1 and RMCP-1 expression was evaluated at RNA and protein levels by real-time PCR and flow cytometry, respectively. PCR products of the expected sizes were amplified from the chromosomal DNA of transfected HEK 293T cells, i.e. 644 bp for H-MCP1 and 737 bp for RMCP-1 constructs. Real-time PCR revealed that the copy numbers of RMCP1 and HMCP1 mRNA per cell were 294 and 500, respectively. Flow cytometry analysis indicated 85% for RMCP-1 and 87% for HMCP-1 expression levels on the surface of transfected cells, when compared with an isotype control. The experiments thus confirmed that the MCP-1 genes were integrated into the HEK 293T genomic DNA and the encoded proteins were stably expressed on the cell surface.